Problems Experienced Counseling Guidance Teachers in Guiding Student Victims of Emotional Violence in Medan - Sinaga, M. Harwansyah Putra; Okkapah, Ruwi Sinta; Syahrani, Juwita; Asiyah, Nur (Pusdikra Publishing, 2024)
Emotional violence targeting students is influenced not only by familial factors but also by the broader social milieu. This form of violence significantly impacts students, particularly affecting their attitudes, character, behavior, emotions, interests, and values. This study aims to explore the challenges faced by guidance and counseling educators in addressing emotional violence among students at Al-Ulum High School in Medan. Employing a descriptive qualitative approach, the research emphasizes descriptive analysis. Data collection involved observation, interviews, and document analysis. Participants included guidance and counseling educators as well as ten students who had experienced emotional violence. Findings reveal the hurdles encountered by educators in assisting students affected by emotional violence. While instances of emotional violence at Al-Ulum High School are relatively low in severity, appropriate guidance and counseling services tailored to these students are essential. Effective management of these services is crucial for addressing the needs of emotional violence victims at the school.